Association between height growth patterns in puberty and stature in late adolescence: A longitudinal analysis in chinese children and adolescents from 2006 to 2016 - Chen, Li; Su, Binbin; Zhang, Yi; Ma, Tao; Liu, Jieyu; Yang, Zhaogeng; Li, Yanhui; Gao, Di; Chen, Manman; Ma, Ying; Wang, Xijie; Wen, Bo; et al. (Frontiers in Endocrinology, 2022)
Introduction: The relationship between characteristic of puberty growth and the stature (height and overweight and obesity) in late adolescence was not clear. We aimed to explore the effects of puberty growth patterns on the stature in late adolescence. Methods: A total of 13,143 children from a longitudinal cohort from 2006 to 2016 in Zhongshan city of China were included. The Preece-Baines Growth Curve was fitted for each individual child, and the age at peak height velocity (APHV), peak height velocity (PHV), and age at take-off (TOA) were obtained from the Preece-Baines model. To compare the difference in height in late adolescence (at 18 years old) at different pubertal height growth patterns (height spurt timing, intensity, and duration), the height at baseline was matched by using the propensity score matching. The log-binomial model was applied to assess the association between the three pubertal height growth patterns (timing, intensity, and duration) and overweight and obesity status in late adolescence, controlling the urbanity and BMI at baseline. Results: After matching the baseline height, boys and girls in three pubertal patterns with early timing (P < 0.01), small intensity (P < 0.01), and short duration (P < 0.01) of height spurt had the lowest final height in the late adolescence. A 16% and 45% increase of risk for overweight and obesity were significantly associated with the early APHV in boy and girls, respectively (relative risk, RR, in boys, 1.16(95%CI: 1.03-1.30), P=0.011; RR in girls, 1.45(1.21-1.75), P<0.001). A 21% and 59% increase of risk for overweight and obesity were significantly associated with small PHV in boy and girls, respectively (RR in boys, 1.21(1.07-1.36), P<0.001; RR in girls, 1.59(1.30-1.95), P<0.001), and an 80% increase of risk for overweight and obesity with small spurt duration in girls (RR=1.80; 95%CI: 1.49, 2.18; P<0.001). Conclusion: Pubertal growth patterns, including earlier puberty oneset timing, smaller puberty intensity, and shorter puberty spurt duration, had a positive association with lower height risks and higher overweight and obesity risks in late adolescence.